The Qur'an Memorization (BTQ) and Juz 30 Memorization Programs, Combined with Innovative Teaching Methods, are One of The Public Schools' Efforts to Attract Public Interest - Wahyuningsih, Esti (International Proceedings of Nusantara Raya, 2024)
This study aims to conduct an epistemological examination of how the Qur'an recitation guidance program (BTQ) combined with Juz 30 memorization and innovative teaching methods can increase public interest in choosing public schools. A qualitative research approach with a case study method was used. The subjects of the study include students, teachers, parents, and principals who are directly involved in the BTQ program. Data was collected through participant observation, in-depth interviews, and document analysis. The results of the study show that the BTQ and Juz 30 memorization programs have succeeded in increasing people's interest in choosing public schools. This is due to several factors, including: Improving the quality of education: This program not only teaches the memorization of the Qur'an but also integrates religious values into academic learning. This provides added value for students and becomes an attraction for the community. Strengthening student character: Through the BTQ program, students are trained to be disciplined, responsible, and have noble character. This is in line with the community's expectations for strong character education. Improving the school's reputation: The success of the BTQ program has improved the school's reputation in the eyes of the public. This school is considered a quality educational institution that is able to produce intelligent and morally upright graduates. Full support from various parties: This program has received full support from teachers, parents, and the community. This support, along with support from employers, colleagues, students, and guardians, is a key factor in the success of the program. The BTQ and Juz 30 memorization program with a combined method is an effective effort to increase public interest in choosing public schools. The program is not only beneficial for students but also for the school and society as a whole.